Tindak Tutur Ilokusi dalam Dialek Sungai Geringging, Pariaman, Sumatera Barat.: Penelitian - Charlina; Ghina'a Jayanthi Putri; Ria Angelina; Ilham Ramadhan; Azzikra; Tiara Isnaini; Reyvano Fathur Aldesra; Putri Ayu Nengsih; Nada Salsabila (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study discusses the forms and functions of illocutionary speech acts in the Minangkabau language, especially the Sungai Geringging dialect used by people in the Pariaman region. This study aims to identify the types of illocutionary speech acts and the socio-cultural context that underlies their use in everyday interactions. The method used is descriptive qualitative with observation data collection techniques, interviews with speakers of the dialect. The results of the study indicate that there are five types of illocutionary speech acts, namely, assertive, directive, commissive, expressive, and declarative, each of which has its own linguistic characteristics and social functions in the local context. In addition, Minang cultural values ​​were found such as how to speak to peers, younger, or older. This influences the form and strategy of using illocutionary speech acts in conversation. These findings enrich the study of regional language pragmatics and contribute to the preservation of the variety of Minangkabau dialects.